Nucleate boiling on prepared surface - Sellamuthu, Santhana Kumari (2012)
This paper reports results from an investigation on the performance of the Rohsenow's type of correlation when applied to the nucleate boiling of water and nanofluids (SiO2) over prepared cylindrical surface (pure stainless, copper embedded stainless steel and brass embedded stainless steel) under open conditions.Various indoor experiments were conducted for different heat inputs varying from 800 to 1600 W and at atmospheric pressure. Experimental data were analyzed by using Rohsenow pool boiling correlation with the help of simple linear regression analysis. The heat transfer flux were estimated in the range of 31.5 to 62.56 kW/m2 ˚C . The nucleate boiling heat flux was observed to increase exponentially with the increase in excess temperature. The average values of constant 'Csf' for Rohsenow correlation for the prepared surface and nanofluids were in range of were found to be 0.0117 and 0.013 respectively.